'No daddy', 'A kind of daddy': words used by donor conceived children and (aspiring) parents to refer to the sperm donor. Issue 4 (3rd April 2018) - Provoost, Veerle; Bernaerdt, Jodie; Van Parys, Hanna; Buysse, Ann; De Sutter, Petra; Pennings, Guido
Abstract: Research has shown that the recipients of donor sperm can experience difficulties finding appropriate language to refer to the donor. Based on two qualitative analysis techniques, namely word count and empirical discourse analysis, we studied the words used to refer to the donor in heterosexual and lesbian (aspiring) parents and in donor conceived children. Findings show that the words used in these households are highly diverse and have at least four different interlinked functions: (1) to position the donor in relation to the nuclear family; (2) to safeguard the role of the social parent; (3) to clarify family structure; and (4) to present a positive picture of the donor. Both parents and children consciously reflect on what words to use to refer to the donor. Although parents try to keep words like 'father' and 'daddy' out of the family narrative, children use these words. These findings show that it is important for healthcare personnel and policy makers to reflect on the careful use of terminology when they address questions around sperm donation because the terminology invokes specific meanings that have an effect on how the recipients and their children perceive the role of the donor.